Charge-Reversible Pro-Ribonuclease Enveloped in Virus-like Synthetic Nanocapsules for Systemic Treatment of Intractable Glioma - Cui, Hongyan; Zhang, Liuwei; Zeng, Shuang; Wang, Yu; Li, Zhen; Wang, Jingyun; Chen, Qixian (ACS applied materials & interfaces, 2022)
We have tailored multifaceted chemistries into the manufacture of artificial virus-like delivery vehicles mimicking viral “intelligent” transportation pathways through sequential biological barriers; these vehicles can acquire the ability to dynamically “program transfer” to their target sites. To accomplish this, we created anionic pro-proteins, which facilitate charge reversal when subject to acidic endosomal pH; in this way, carboxylation reactions are performed on proteins with amine-reactive cis-aconitic anhydride. Electrostatic associations then initiate the envelopment of these pro-proteins into multilayered nanoarchitectural vehicles composed of multiple-segmental block copolycationic cyclic Arg-Gly-Asp (RGD)-poly(ethylene glycol)(PEG)-GPLGVRG-polylysine(thiol). Therefore, upon the pro-proteins’ initial binding to the tumors via the protruding RGD ligands, the bio-inert PEG surroundings are detached through the enzymolysis of the intermediate GPLGVRG linkage by tumor-enriched matrix metalloproteinases, unveiling the cationic polylysine palisade and imparting intimate affinities to the anionic cytomembranes of the targeted tumors. Essentially, through their active endocytosis into the subcellular endosomal compartments, the pro-proteins are made capable of retrieving the original amine groups through a charge reversal decarboxylation process, consequently eliciting augmented charge densities (charge nonstoichiometric protein@polylysine(disulfide)) to disrupt the anionic endosomal membranes to facilitate translocation into the cytosol. Eventually, the active protein payloads can be liberated from nonstoichiometric protein@polylysine(thiol) by the disassembly of polylysine palisade upon the cleavage of disulfide crosslinking in response to the very high level of glutathione in the cytosol, thereby contributing toward extreme cytotoxic potency. Hence, our elaborated virus-mimicking platform has demonstrated potent antitumor efficacy through the systemic administration of ribonucleases, which will consequently lead to an innovative new therapeutic method by which proteins could reach intracellular targets.